DETERMINANTS OF HYPERTENSION PREVENTION BEHAVIOR IN WOMEN OF REPRODUCTIVE AGE (WRA) IN TAKERAN SUB-DISTRICT, MAGETAN REGENCY: Determinan Perilaku Pencegahan Hipertensi pada Kelompok Wanita Usia Subur di Kecamatan Takeran Kabupaten Magetan - Septiana, Mia; Kusumawati, Yuli (Jurnal Berkala Epidemiologi, 2024)
Background: Basic health research data (Riskesdas) in 2018 shows that hypertension is one of the highest causes of death in Indonesia, reaching 6.8%. If hypertension occurs in women of childbearing age, the risk of complications, morbidity, and even death will be higher due to the risk of eclampsia during labor. Efforts to prevent hypertension in women of Reproductive age (WRA) need to be improved through increasing hypertension prevention behavior. Various factors can influence hypertension prevention behavior. Purpose: This study aims to analyze the determinants of hypertension prevention behavior in a group of women of reproductive age in Takeran District, Magetan Regency. Methods: This observational study was conducted with a cross-sectional design. The research sample was women of Reproductive age in the Takeran District, Magetan Regency, with as many as 276 people. The sampling technique used purposive sampling technique. This research was conducted in March 2022, using data analysis using the Chi-Square Test and Logistic Regression Test. The instruments used in this research were questionnaires and informed consent. Results: There was a relationship between knowledge (p = 0.02), self-efficacy (p = 0.00, family support (p = 0.00, and support from health workers (p = 0.000) with hypertension prevention behavior, but there was no relationship between age (p = 1,00) and attitude (p = 0.49) with hypertension prevention behavior. Conclusion: The strongest determinant factor for hypertension prevention behavior in the group of women of Reproductive age was self-efficacy. Good self-efficacy can influence good hypertension prevention behavior.